2008
DOI: 10.1071/rd07175
|View full text |Cite
|
Sign up to set email alerts
|

In vitro maturation of porcine oocytes with retinoids improves embryonic development

Abstract: Abstract. In the present study, the effects of retinoid metabolite administration during in vitro maturation (IVM) on oocyte maturation, parameters of in vitro fertilisation (IVF) and embryo development were examined. Varying concentrations of 9-cis retinoic acid (RA; 0, 5, 50 and 500 nm; Experiment 1) and all-trans retinol (ROH; 0, 125, 1250 and 12 500 nm; Experiment 2) were included in the maturation medium. Cumulus-oocyte complexes were matured in vitro and inseminated with frozen-thawed spermatozoa. Presum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 37 publications
1
44
2
Order By: Relevance
“…The present results are in disagreement with those obtained in porcine IVF, where it has been reported that treatment of oocytes with all-trans retinol resulted in better embryo cleavage compared with control, this enhancement was not reflected in blastocyst development, whereas the presence of 5 nm 9-cis retinoic acid in the IVM medium significantly increased the blastocyst formation rate, suggesting that 9-cis-retinoic acid may play an important role during IVM (Alminana et al, 2008). A possible explanation for these discrepancies could be the different IVM conditions used by these authors, where the oocytes are matured for 20-22 h with supplements and another 20-22 h without supplements.…”
Section: Discussioncontrasting
confidence: 99%
“…The present results are in disagreement with those obtained in porcine IVF, where it has been reported that treatment of oocytes with all-trans retinol resulted in better embryo cleavage compared with control, this enhancement was not reflected in blastocyst development, whereas the presence of 5 nm 9-cis retinoic acid in the IVM medium significantly increased the blastocyst formation rate, suggesting that 9-cis-retinoic acid may play an important role during IVM (Alminana et al, 2008). A possible explanation for these discrepancies could be the different IVM conditions used by these authors, where the oocytes are matured for 20-22 h with supplements and another 20-22 h without supplements.…”
Section: Discussioncontrasting
confidence: 99%
“…The beneficial effects of retinol metabolites on in vitro cytoplasmic maturation and embryo development have been previously described [5,6,12,20,25] however there are no reports about the simultaneous effects of t-RA and co-culture systems of granulosa cells on the developmental potency of cumulus-free immature oocytes. Following our previous observation [22], in the present study we have shown that the use of 2 μM t-RA in maturation medium with granulosa cell monolayer improves developmental competence of naked immature mice oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we have shown that the use of a physiological dose of all-trans retinoic acid (t-RA; 2 μM) during in vitro maturation and under precise conditions could improve both maturation and developmental competence of denuded immature mouse oocytes [22]. Therefore, based on this and other studies [5,6,12,[19][20][21][22] we assume that the cumulus granulosa cells might be a target for added RA during in vitro maturation, which could improve embryo development. In this study, we evaluate the effects of t-RA in association with a co-culture granulosa cell monolayer on the IVM of naked immature mice oocytes and then follow them until the blastocyst stage.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations